Self-expression values, loyalty generation, and support for authoritarianism: evidence from the Arab world. Issue 7 (3rd October 2018) - Ciftci, Sabri
ABSTRACT: This study examines the micro foundations of political support in Arab polities. Most Arab states rank highly in aggregate human development or economic wealth, but they lag behind in democracy defying the predictions of modernization theory. Modernization and human development perspective implies that increased resources and self-expression values will induce critical political outlooks toward the regime. This study questions the applicability of this theory to the Arab region and proposes that colonial state formation history, international patron–client relations, and the domestic patronage networks have more leverage in explaining regime support in the Arab region. A series of multilevel and fixed effects regression estimations utilizing the Arab Democracy Barometer reveal that modernization perspective has some relevance. However, world system theory inspired patron–client perspective and loyalty generation through domestic distributive mechanisms play a greater role in shaping political attitudes. The results provide important insights about micro foundations of Arab authoritarianism and the differential utility of emancipative values formed in the context of hierarchical world order.